2008
DOI: 10.1126/science.1159519
|View full text |Cite
|
Sign up to set email alerts
|

Riboswitches in Eubacteria Sense the Second Messenger Cyclic Di-GMP

Abstract: Cyclic di-GMP is a circular RNA dinucleotide that functions as a second messenger in diverse species of bacteria to trigger wide-ranging physiological changes, including cell differentiation, conversion between motile and biofilm lifestyles, and virulence gene expression. However, the mechanisms used by cyclic di-GMP to regulate gene expression have remained a mystery. We demonstrate that cyclic di-GMP in many bacterial species is sensed by a riboswitch class in mRNA that controls the expression of genes invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
746
2
7

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 637 publications
(784 citation statements)
references
References 22 publications
13
746
2
7
Order By: Relevance
“…These include proteins containing PilZ domains, or even degenerate GGDEF/EAL domains, which have been found to bind c-di-GMP and regulate related downstream processes such as motility and virulence (Amikam & Galperin, 2006;McCarthy et al, 2008;Navarro et al, 2009;Newell et al, 2009;Pratt et al, 2007;Ryjenkov et al, 2006). Besides mediating protein-protein interactions, c-di-GMP has been shown also to regulate protein translation through two classes of c-di-GMP riboswitches (Smith et al, 2011;Sudarsan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These include proteins containing PilZ domains, or even degenerate GGDEF/EAL domains, which have been found to bind c-di-GMP and regulate related downstream processes such as motility and virulence (Amikam & Galperin, 2006;McCarthy et al, 2008;Navarro et al, 2009;Newell et al, 2009;Pratt et al, 2007;Ryjenkov et al, 2006). Besides mediating protein-protein interactions, c-di-GMP has been shown also to regulate protein translation through two classes of c-di-GMP riboswitches (Smith et al, 2011;Sudarsan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These RNA domains, known as riboswitches, are components of a cis-acting genetic control module, which bind to a diverse array of metabolites and control the genes involved in the biosynthesis or degradation of these metabolites (Winkler and Breaker 2005). Riboswitches have also been found that bind second-messenger molecules to regulate fundamental cellular processes (Sudarsan et al 2008). Structural changes within the riboswitch occur upon ligand binding, allowing the riboswitch to interact with an expression platform to modulate gene expression by effects on transcriptional or translational efficiency (Yarnell and Roberts 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations indicate that c-di-GMP can act as a riboswitch, binding specific elements (aptamers) in the UTRs of some mRNAs and affecting their stability (Sudarsan et al, 2008). The pgaABCD transcript is characterized by a rather long UTR (234 nt; Wang et al, 2005) and is regulated at the level of mRNA stability by the CsrA protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, YddV does not seem to regulate pgaABCD expression by modulating CsrA activity. Since c-di-GMP has been shown to act as a riboswitch, and to be able to increase the chemical and functional half-life of mRNA carrying c-di-GMP-responding elements (Sudarsan et al, 2008), we tested the possibility that the yddV gene affects pgaABCD mRNA stability via its DGC activity. mRNA decay kinetics experiments showed that the pgaA transcript has a half-life of~1.5 min in the MG1655 strain; yddV inactivation did not affect pgaABCD mRNA stability in the MG1655 background (data not shown), suggesting that yddV-dependent pgaABCD regulation is not mediated by mRNA stabilization.…”
Section: Regulation Of Pgaabcd Expression By Dgcsmentioning
confidence: 99%
See 1 more Smart Citation